Brazil as a BRICS in the Shaping of the South American Region and Global Politics - Salgado Espinoza, Raúl (2016)
The BRICS (Brazil, Russia, India, China and South Africa) states as emerging powers have positioned themselves as the leading regional international actors and together are challenging the unilateral world leadership. This article presents the argument that the prospect of being a BRICS state helps each nation to project itself as a political world player, but could torpedo the projection of positioning as a regional leader as in the case of Brazil in the South American region. Other factors such as the influence of external economic, political and military forces might contribute to slowing down and even constraining the consolidation of Brazil as a leader of the region. In order to illustrate this, this article employs Modelski’s geopolitical model to explain the rise and decline of world powers in combination with some elements of the Positioning Theory. The evidence is based on a set of qualitative data and employs a qualitative content analysis for analyzing and interpreting the data.